ANTI-INFLAMMATORY ACTIVITY AND PHYTOCHEMISTRY OF EXTRACTS FROM THE ROOT BARK OF CALOTROPIS PROCERA (AIT.) R. BR. HEPATOPROTECTIVE MEDICINAL PLANT FROM BURKINA FASO - SOMBIÉ, ERNEST NOGMA; OUÉDRAOGO, NOUFOU; HILOU, ADAMA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study aimed to assess the anti-inflammatory and antioxidant properties in vitro of Calotropis procera root bark. Methods: Anti-inflammatory activities of the ethanolic extract of root bark of C. procera and its fractions were evaluated on lipoxygenase and xanthine oxidase (XO). Antioxidant activity was evaluated by trapping the 2,2-diphenylpicrylhydrazyl (DPPH) radical, hydrogen peroxide (H2O2), by the reducing power ferric reducing antioxidant power. Inhibitory powers of lipid peroxidation and of degradation of D-deoxyribose as well as the contents of phenolic and triterpene compounds were also evaluated. Results: Ethanolic extract showed interesting anti-inflammatory and antioxidant activities. Butanol fraction which is one of richest fractions for flavonoids (17.38±0.13 mg EQ/10 g extracts) showed the best percentages for inhibitions of XO (60.14±4.89%), degradation of D-deoxyribose (81.04±0.77%), and the DPPH radical (71.43±6.35%). Dichloromethane fraction which is the richest in triterpenes (1067.02±5.77 mg UAE/g extracts) showed the best percentages for inhibitions of lipoxygenase (56.45±1.15%) and of lipid peroxidation (82.45±0.73%). Ethyl acetate and residual aqueous fractions, respectively, showed the best activities of inhibiting H2O2 (75.38±0.76%) and for iron-reducing capacity (23.51±1.69 mg EAA/g extracts). Conclusion: Ethanolic extract from C. procera root bark and its fractions, their particular the butanol and dichloromethane one, has anti-inflammatory and antioxidant properties which could prevent or attenuate liver injury and its complications.